Responsible Knowing in an Age of Ignorance: Feminist Critiques and Integral Possibilities of Sri Aurobindo - ANTHONY, Baiju P. (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
Traditional epistemology treats ignorance as a passive absence of knowledge, overlooking its active production within socio-political structures. Feminist epistemology challenges this view by conceptualizing ignorance as a politically charged phenomenon shaped by power, privilege, and epistemic injustice. Drawing on thinkers such as Lorraine Code, Miranda Fricker, José Medina, and Nancy Tuana, this paper argues that ignorance is socially constructed and ethically consequential. Integrating Sri Aurobindo’s philosophy of integral knowledge, it further expands ignorance beyond social structures to include metaphysical and ontological dimensions. The paper proposes epistemic responsibility and conscious knowing as forms of resistance that enable epistemic justice and transformative understanding.